Research on the Earth Reflected Solar Spectral Radiation Observation System Based on the Lagrange L1 Point of the Earth–Moon System - Cong Zhao; Kai Wang; Shuqi Li; Xin Ye; Xiaolong Yi; Ye Jiang; Wei Fang (Remote Sensing)
We propose an observation system based on the Lagrange L1 point of the Earth–Moon system to observe solar spectral radiation reflected from the Earth, enabling continuous hyperspectral observation of the Earth’s hemisphere. The system can observe the solar spectral radiation reflected by the Moon, with its data applicable to on-orbit spectral radiation calibration. In this paper, the spectral irradiance at the entrance pupil of the Earth spectral radiation observation system (ESROS) is analyzed, and the optical design of the ESROS is introduced. An off-axis two-mirror telescope system, a coupling system of a microlens array and a fiber bundle, and an optical splitting system based on concave grating are used to achieve the full field of view hyperspectral splitting and miniaturization of the instrument. Finally, the stray radiation suppression of the instrument is introduced. The results show that the spectral resolution of the system is better than 5 nm in the 380–1000 nm band, and the spectral resolution is better than 10 nm in the 1000–1700 nm band. When observing the Earth, the signal-to-noise ratio is greater than 200. The external stray radiation suppression reaches the order of 10−9. The ESROS will provide crucial data support for researching global energy balance, climate change, and the spectral characteristics of exoplanets, facilitating planetary science and the exploration of extraterrestrial life.